Knowledge and Beliefs towards Malaria and Associated Factors among Residents of the Town of Douala, Cameroon - Loick Pradel Foko Kojom; Leopold Gustave Lehman (Archives of Current Research International, 2018)
Malaria is still a great public health concern in all endemic areas despite many control interventions by the national malaria control programme (NMCP) for this last decade. Some researchers pointed out the importance of the implication of population in for the success of control interventions. This study aimed at determining the level of knowledge and beliefs towards malaria as well as associated factors among individuals living in Douala. This was a household-based cross-sectional study. A total of 1696 individuals were included from November 2015 to January 2016 in three districts (Makepe, Deido and Bonamoussadi) of the town of Douala, Cameroon. A pre-tested semi-structured questionnaire was used to collect data from participants. Participants were mainly females (50.2%), aged 25-35 years (36.4%) and had attended university level (57.2%). The level of knowledge of participants was high on transmission, clinical aspects and prevention of malaria although some misconceptions were reported. Most of the respondents (98.1%) perceived bed net as a good prevention tool against malaria. The potential harmfulness of antimalarial drugs was not perceived by 37.4% of participants. The level of knowledge on transmission and prevention was three folds (OR = 2.77; P = .0125) and six folds (OR = 6.34; P = .0148) higher in those having attended university level compared to illiterate respondents respectively. Furthermore, gender and age of participants have significantly (P < .05) influenced the knowledge of malaria. Awareness on malaria is high among residents of the town of Douala but there is a need to develop new sensitization strategies towards people with poor level of education.